159 LUNG FUNCTION AS A PREDICTOR OF LOWER AIRWAY DISEASE IN ADULTS WITH RHINITIS. Issue 1 (1st January 2007) - Wright, B.; Sherrill, D.; Guerra, S.
Abstract : It has been well established through scientific research that upper airway inflammation can lead to the development of lower airway disease. Although the mechanism by which this occurs remains unknown, rhinitis has been characterized as an independent risk factor for developing both adult-onset asthma and chronic cough. The purpose of this research is to create a profile of risk factors among rhinitis patients for development of asthma, chronic cough, and respiratory symptoms and to determine if spirometric values of FEV1, FEF25-75, FEV1 /FVC ratio can be used as predictors of development of these diseases and symptoms. We used data from the prospective population-based cohort of the Tucson Epidemiological Study of Airway Obstructive Disease (TESAOD). Subjects with rhinitis were evaluated for the incidence of asthma, wheeze, and chronic cough using Cox proportional models. Marginal analysis was used to determine which parameters to include in the final model. In the case that multiple spirometric values were significant predictors, model selection was based on Akaike's Information Criterion (AIC). We identified 3054 TESAOD participants ≥ 20 years old at the baseline survey. Of these individuals, 1, 111 (36.3%) reported having rhinitis but did not have asthma. Pulmonary function data were available for 1, 036 (93%) of these subjects. Marginal analysis revealed that both FEV1 and FEF25-75 were significant predictors, but FEV1 was selected based on AIC. After adjustment for potential confounders, final Cox regression analysis revealed that FEV1 was a significant predictor for acquiring a physician confirmed diagnosis of asthma (adjusted hazard ratio [HR] 0.975, 95% CI 0.962-0.987, p < .0005). This means that greater values of FEV1 are associated with a lower risk. This effect remained significant after removal of subjects reporting wheeze (adjusted HR 0.974, 95% CI 0.955-0.994, p = .012). FEV1 was also a significant predictor for the development of wheeze among rhinitis patients reporting no asthma or a prior history of wheeze at the baseline survey (adjusted HR 0.984, 95% CI 0.976-0.992, p < .0005). We also found a borderline significant association between the ratio FEV1/FVC and development of chronic cough (adjusted HR 0.985, 95% CI 0.968-1.003, p = .097). We conclude that spirometry can be useful to identify rhinitis patients who are most likely to develop lower airway disease and its symptoms, although its sensitivity and specificity in this framework remain to be determined.